The analysis of the social media impact on the millennial generation behavior and social interactions - Ardi, Zadrian; Putri, Shania Andrisa (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2021)
Social media is used to obtain various information and is also used to interact with other people. Even though they are in different regions and even countries, interactions can still be done by utilizing this technology. Even the latest news developments, quality improvements, and business-related dissemination have been effectively using social media platforms. This development makes social media one of the most dominant technology platforms for internet use. Nevertheless, in some cases, there are negative impacts that arise from social media use, especially those related to the interaction between users in it. The millennial generation, who are the primary target users of this platform, felt a significant impact. This article aims to analyze the general impacts of social media use on millennials regarding social behavior and interactions. The views of the analysis of this manuscript are seen from various points of view.